2019
DOI: 10.1002/cam4.2567
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of gastrointestinal neuroendocrine neoplasm metastasis in liver, lung, bone, and brain: A population‐based study

Abstract: BackgroundNeuroendocrine neoplasm is a rare solid tumor. Metastatic pattern of the gastrointestinal neuroendocrine neoplasm (GI‐NEN) has not been fully explored.MethodsData were obtained from the Surveillance, Epidemiology, and End Results (SEER) database (SEER‐9 registry) from 1973 to 2015. Incidence was estimated by Joinpoint regression analyses. Data with additional treatment fields of GI‐NEN were extracted from the SEER‐18 registry from 1 January 2010 to 31 December 2015. A total of 14 685 GI‐NEN patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 17 publications
(33 reference statements)
1
37
1
Order By: Relevance
“…Additionally, distant metastasis was an independent risk factor affecting prognosis. Studies related to prognosis for type 3 g-NETs were scare, but several studies of gastroenteropancreatic NETs[ 34 - 36 ] had shown that distant metastasis was significantly associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, distant metastasis was an independent risk factor affecting prognosis. Studies related to prognosis for type 3 g-NETs were scare, but several studies of gastroenteropancreatic NETs[ 34 - 36 ] had shown that distant metastasis was significantly associated with prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 However, the detection of these cancer markers still can not be used to determine the early stage of lung cancer, but only as a risk indicator for lung cancer. 6 Some invasive tests can provide evidence but may lead to pneumothorax and related complications. Traditional medical imaging techniques, such as X-ray 7−10 and magnetic resonance imaging (MRI), 11−13 can only detect lung cancer in the midstage, and can not accurately diagnose early lung cancer and stage lung cancer.…”
Section: ■ Introductionmentioning
confidence: 99%
“…At the time of neuroendocrine tumour (NET) diagnosis, there are synchronous metastases in already 21%-55% of the patients, [116][117][118][119] of which 72%-82% are located in the liver. 118,120 In the overall NET population, a median survival rate of 112 months is reported, 119 and drops to 38 months in patients with liver metastases. 120 Gastroenteropancreatic NETs (GEP-NET) represent 61% of all NETs, 121 and harbour the highest risk for metastasis.…”
Section: Me Ta S Tatic Neuroendocrine Tumour Smentioning
confidence: 99%
“…118,120 In the overall NET population, a median survival rate of 112 months is reported, 119 and drops to 38 months in patients with liver metastases. 120 Gastroenteropancreatic NETs (GEP-NET) represent 61% of all NETs, 121 and harbour the highest risk for metastasis. 118 Resection of the primary tumour is critical to maximize OS.…”
Section: Me Ta S Tatic Neuroendocrine Tumour Smentioning
confidence: 99%
See 1 more Smart Citation